P140 Identification of affimers that bind to the IL-7R and inhibits the IL-7 signalling cascade. (March 2019) - Perez-Witzke, D; Tiede, C; Robinson, JI; Tomlinson, D; Emery, P; Ponchel, F
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: IL-7R is a heterodimer constituted by the IL-7R alpha (α) chain (CD127) and the common gamma (g) chain (CD132). IL-7 binding to IL-7R expressed on CD4+ T cells induces a survival signal. The IL-7/IL-7R signalling axis has been validated as a therapeutic target for treatment of both T-cell driven autoimmune diseases (AIDs) 1 and T Acute Lymphoblastic Leukaemia (T-ALL). 2 Affimers are small and stable artificial proteins which bind with nanomolar affinities to human proteins and can block protein-protein interactions. 3 They are becoming widespread owing to their stability, ease of production and versatility. Objectives: Identify Affimers that recognise the IL-7Rα and inhibits the IL-7 signalling cascade. This may result in an attractive approach for the treatment of both T-cell driven autoimmune diseases and T-ALL. Methods: The type-II Affimer library (10 10 ) was interrogated by Phage display using fully glycosylated human IL-7Rα ectodomain (ECD). PhageELISA and DNA sequencing were used to either obtain or elucidate the unique binders (Affimers), respectively. Affimers were produced as His-Tagged proteins (∼13 kDa) in E. coli and purified using IMAC. Affimer binding to IL-7Rα was confirmed by pull-down assays (soluble) and Flow cytometry (membrane). An IL-7 reporter assay using HEK-IL7R (HEK293 cells stably transfected with the IL-7R) was developed and the biological effect of the Affimers was elucidated. Results: We have screened an Affimer library using human ECD-IL7Rα and after three consecutive panning rounds, 20 Affimers were raised as shown by PhageELISA and DNA sequencing. From these, 17 were able to pull-down the soluble ECD-IL7Rα and 7 stained specifically HEK-IL7R cells (by flow cytometry using anti-His Tag Abs). Finally, we have identified 3 Affimers (1, 42 and 96) that showed inhibition of the IL-7 signalling cascade on HEK-IL7R cells. Conclusions: Our work demonstrates the possibility of screening an Affimer library for a cytokine-receptor target, and selecting specific binders, some of which showed the desired antagonist activity of the cytokine signalling cascade. IL-7 itself is a validated target, so this work offers an alternative to antibody-mediated protein interference. With further biological validation including animal models, it may even offer a novel therapeutic tool for AIDs and T-ALL. References: Ponchel F, et al. Advances in Medicine and Biology 2014;77. Cramer, SD, et al. Blood 2016;128:473–78. Tiede, et al. eLife 2017;6:e24903. Acknowledgements: We would like to thanks Prof. S. Savvides, Dr. K. Verstraete (VIB, Belgium) and Dr. Joao Barata (IMM, Portugal) for their contribution on this work. Disclosure of Interest: None declared.